Meaningful Gamification in Ecotourism: A Study on Fostering Awareness for Positive Ecotourism Behavior - Rosmadi, Amalia; Zhou, Wuzhong; Xu, Yuanyuan (Sustainability, 2024)
Research into ecotourism behavior in China through meaningful gamification offers a promising strategy for enhancing sustainable tourism practices. With the rapid growth of China’s ecotourism sector, understanding and influencing visitor behaviors is crucial. This study focuses on meaningful gamification elements—exposition, information, engagement, and reflection—as a technique to nurture positive intentions towards ecotourism behavior, increase environmental awareness, educate tourists, and promote sustainable practices in an interactive way. Aligning with China’s technological and sustainability goals, this research introduces the Meaningful Gamification Elements for Ecotourism Behavior (mGEECO) model. This model is analyzed using Structural Equation Modeling (SEM)–Partial Least Squares (PLS) to test hypotheses related to the relationship between gamification elements and ecotourism intentions, grounded in Stimulus–Organism–Response (SOR) theory. The findings show that meaningful gamification significantly enhances positive intentions towards ecotourism by improving Environmental Attitude, Awareness of Consequences, and Ascription of Responsibilities. In conclusion, this approach raises awareness of sustainability practices and fosters a sense of responsibility, potentially leading to a more balanced and responsible ecotourism industry in China, benefiting both the environment and local communities while enhancing visitor experiences.